DNA Testing Methodology for the Evaluation of Susceptibility to Scrapie in Tsurcana Sheep - Dana-Iuliana Neață; Maria-Mihaela Antofie; Teodor Vintilă (Scientific Papers Animal Science and Biotechnologies)
Scrapie, first reported in the 18th century, has led to considerable economic losses by affecting the livestock industry. This disease is a transmissible spongiform encephalopathy that mainly affects sheep and goats and is caused by the accumulation of prion protein in an abnormal form (PrPSc) in the nervous system of animals. The identification of genetic polymorphisms in the PRNP gene has allowed the development of effective genetic tests for the detection of susceptibility to Scrapie. In many European countries, these tests are being used to select resistant animals, thereby reducing the risk of spreading the disease in sheep flocks. The method applied in this research to identify susceptible or resistant genotypes to Scrapie in sheep, applies DNA tests made from biological samples such as hair, blood and other tissues. By analysing polymorphisms in the PRNP gene at codons 136, 154 and 171, the animals were classified into five different risk categories.  Early genotyping of sheep at the PRNP locus allows rapid selection of genotypes conferring resistance to this disease, thus contributing to improving the genetic resistance of sheep breeds.